Case Report: Congenital Intracranial Kaposiform Hemangioendothelioma Treated With Surgical Resection - Yingjie Cai; Jiayi Li; Wei Yang; Nan Zhang; Hailang Sun; Weiping Zhang; Ming Ge (Frontiers in Surgery, 2022)
BackgroundKaposiform hemangioendothelioma (KHE) is a locally aggressive but non-metastatic vascular neoplasm. Most studies have been restricted to small case series of limited generalizability. Intracranial KHE is extremely rare with only three cases reported in the literature. Here, we report a case of congenital intracranial KHE who underwent surgical resection, and no lesion recurrence was seen during the follow-up period of 13 months.Case DescriptionA 2-month-old boy initially presented with a left temporal mass following birth. Antenatal ultrasound at 36 weeks of gestation demonstrated a hyperechoic signal present in the left frontal lobe, with clear borders and irregular morphology. There were neither cutaneous abnormalities nor other neurologic examination abnormalities. No laboratory abnormality was identified. Computed tomography (CT) scans suggested that a massive hematoma was noted under the left frontal skull plate, with a little subdural hemorrhage in the adjacent temporal area. The adjacent meninges enhanced and thickened on contrasted T1 magnetic resonance (MR). After the multidisciplinary diagnostic assessment, the surgery was performed by the left frontotemporal craniotomy approach. The operation was extremely difficult. We completely removed the tumor, and the involved dura and brain tissue were resected with the lesion in a piecemeal fashion. On postoperative-day (POD) 3 and POD 14, the head CT re-examination revealed that cerebral perfusion improved gradually. The MRI of 6- and 12-month after operation showed no local recurrence or metastasis.ConclusionsIntracranial KHE is difficult to diagnose early and the prognosis has been uniformly poor. We supposed that meticulous intraoperative hemostasis is the key for a successful operation, and the radical resection of the tumor and involved structures are essential to reduce recurrence.